The Effect of Polypharmacy on Drug Interactions in Rheumatoid Arthritis Patients: A Literature Review - Vania Putri Risyhade; Asep Sukohar; Muhammad Maulana; Rasmi Zakiah Oktarlina (Sean Institute, 2025)
Rheumatoid arthritis is a chronic autoimmune disease that is progressive in nature and requires long-term therapy involving a combination of multiple drugs. The complexity of treatment increases the risk of polypharmacy, which in turn can trigger drug interactions and reduce the safety and effectiveness of therapy. This literature review aims to describe the relationship between polypharmacy and the potential for drug interactions in patients with rheumatoid arthritis, while considering the importance of monitoring drug use in clinical practice. The writing method was carried out by reviewing various national and international studies related to polypharmacy and drug interactions in rheumatoid arthritis patients. The findings indicate that the concurrent use of several medications, particularly combinations of nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and disease-modifying antirheumatic drugs (DMARDs), can lead to moderate to severe interactions that may cause serious adverse effects such as hepatotoxicity, renal impairment, and bleeding. Furthermore, the greater the number of drugs used, the higher the likelihood of harmful effects, both due to pharmacokinetic and pharmacodynamic interactions. This condition highlights the need for healthcare professionals to regularly evaluate prescribed medications, adjust dosages, and educate patients about the safe and rational use of drugs. These efforts are essential to minimize adverse effects, improve treatment adherence, and achieve optimal therapeutic outcomes in patients with rheumatoid arthritis.